Solid state synthesis and room temperature magnetic properties of iron phosphide nanoparticles - Singh, N.; Khanna, P. K.; Joy, Pattayil Alias (Journal of Nanoparticle Research, 2009)
Room temperature magnetic properties have been achieved for nano-crystalline iron phosphide synthesized from the direct solid state reaction of iron chloride and tri-octylphosphine (TOP). The magnetization continuously increased with higher magnetic fields, indicating a super-paramagnetic behavior. It is observed that room temperature magnetism is possible for the material showing antiferromagnetic nature at low temperatures. In the present synthesis, TOP acted as a source of phosphorus as well as a surfactant. X-ray diffraction (XRD) studies revealed that the black powder is a mixture of FeP and Fe(2)P. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) showed elongated as well spherical particles. Energy dispersion X-ray analysis (EDAX) confirmed a non-stoichiometric iron phosphide. Presence of TOP was confirmed by infra-red (IR) spectroscopy, and thermo-gravimetric analysis (TGA) indicated about 6% wt. loss due to presence of organics.
Keywords: Iron phosphide; Semiconductors; Solid state reaction; synthesis; XRD

Highly sensitive and fast responding CO sensor based on Co3O4 nanorods - Patil, Dewyani; Patil, Pradip; Subramanian, Vijayanand; Joy, Pattayil Alias; Potdar, Hari S. (Talanta, 2010)
Co3O4 nanorods (diameters similar to 6-8 nm and lengths similar to 20-30 nm) were synthesized for the first time through a simple co-precipitation/digestion method by calcination of cobalt hydroxyl carbonate in air and their CO gas sensing properties were investigated. The Co3O4 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 6.55-50 ppm CO gas at 250 degrees C), extremely rapid response (similar to 3-4s), fast recovery (similar to 5-6s), excellent repeatability, good selectivity and lower operating temperature (similar to 250 degrees C). Furthermore, the Co3O4 nanorods are able to detect up to 5 ppm for CO with reasonable sensitivity (similar to 3.32) at an operating temperature 250 degrees C and they can be reliably used to monitor the concentration of CO over the range (5-50 ppm). The experimental results clearly demonstrate the potential of using the Co3O4 nanorods as sensing material in the fabrication of CO sensors. Plausible CO sensing mechanism of the Co3O4 nanorods is also discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CO sensor; Co3O4 nanorods; HRTEM; Semiconductor gas sensors; XPS; XRD

Preparation and characterization of flexible ferromagnetic nanocomposites for microwave applications - Thomas, Teena; Kanoth, Bipinbal P.; Nijas, C. M.; Joy, Pattayil Alias; Joseph, Joseph M.; Kuthirummal, Narayanan; Thachil, Eby T. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2015)
Magnetic Fe3O4 nanoparticles (similar to 20 nm) were synthesized using the chemical co-precipitation method with a view of developing flexible and easily processable ferromagnetic materials with high mouldability to be used as microwave absorbers. The nanoparticles prepared were incorporated into natural rubber through latex stage processing. This novel processing method gives better dispersion of particles in the rubber matrix. The composites were characterized using XRD, SEM, vibrating sample magnetometer, dynamic mechanical analyzer, cavity perturbation, thermogravimetry (TGA), and Fourier transform infrared photoacoustic spectroscopy (FTIR-PAS). A notable improvement in the mechanical properties of composites was observed upon adding Fe3O4 particles. Magnetic and microwave characteristics of the composites indicate the formation of a flexible ferromagnetic material with good microwave absorption characteristics. (C) 2015 Published by Elsevier B.V.
Keywords: Fe3O4; Ferromagnetic; FTIR-PAS; Microwave absorption; Natural rubber; SEM; XRD